The Ethics of Real-Time EMS Direction: Suggested Curricular Content. Issue 2 (14th February 2018) - Brenner, Jay M.; Aswegan, Andrew L.; Vearrier, Laura E.; Basford, Jesse B.; Iserson, Kenneth V.
Abstract: Ethical dilemmas can create moral distress in even the most experienced emergency physicians (EPs). Following reasonable and justified approaches can help alleviate such distress. The purpose of this article is to guide EPs providing Emergency Medical Services (EMS) direction to navigate through common ethical issues confronted in the prehospital delivery of care, including protecting privacy and confidentiality, decision-making capacity and refusal of treatment, withholding of treatment, and termination of resuscitation (TOR). This requires a strong foundation in the principles and theories underlying sound ethical decisions that EPs and prehospital providers make every day in good faith, but will now also make with more awareness and conscientiousness. JM Brenner, AL Aswegan, LE Vearrier, JB Basford, KV Iserson .The ethics of real-time EMS direction: suggested curricular content .Prehosp Disaster Med .2018 ;33 (2 ):201 –212 .